NILAI-NILAI PENDIDIKAN DALAM NOVEL MERRY RIANA MIMPI SEJUTA DOLAR KARYA ALBERTHIENE ENDAH - Agatha, cornelia; Martono, Martono; Wartiningsih, Agus (Universitas Tanjungpura, 2023)
This study aims to describe and interpret the results of an analysis of education values in the novel Merry Riana Mimpi Sejuta Dolar by Alberthiene Endah, as well as develop a learning design using the novel as learning material. This study uses a descriptive menthod with a qualitative research form. The approach used is the socialogy of literature. The source of data in this research is novel Merry Riana Mimpi Sejuta Dolar by Alberthiene Endah. Data collection technique using documentary study technique. Data analysuis techniques by means of data collection, data reduction, data presentation, and drawing conclusion. The results of this study indicate the educational values contained in novel Merry Riana Mimpi Sejuta Dolar, namely the value of moral education and the value of religious education. The values of moral education include responsibility, never give up, perseverance, hard work, and courage. The values of religious education include praying, believing, being grateful, and being sincere in the novel. Researchers have designed a lesson plan that utilizes the novel as learning material, specifically to achieve KD 3.9 and 4.9 in class XII SMA.